2003
DOI: 10.1097/00005110-200301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Documentation Time During Implementation of an Electronic Medical Record

Abstract: Despite charting concurrently on both paper and computer, the amount of time spent on documentation was not excessive, and was consistent with previous studies in which neither electronic nor "double charting" occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 24 publications
0
41
3
Order By: Relevance
“…17,22 Activities are classified based on research purposes, and most would divide nursing activities into five categories: direct care, indirect care, documentation, unit-related activity, and personal activity. [13][14][15]17,23 To understand the work of nurses and properly record their observed activities on the instrument, each observer must have clinical knowledge, such as a senior nurse with nursing experience 13 or a trained medical student 14 or senior nursing students. 15 For limiting the interrater reliability, related training and tests must be given to each observer, including the data collection format, coding, description, and guidance.…”
Section: Work Sampling Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…17,22 Activities are classified based on research purposes, and most would divide nursing activities into five categories: direct care, indirect care, documentation, unit-related activity, and personal activity. [13][14][15]17,23 To understand the work of nurses and properly record their observed activities on the instrument, each observer must have clinical knowledge, such as a senior nurse with nursing experience 13 or a trained medical student 14 or senior nursing students. 15 For limiting the interrater reliability, related training and tests must be given to each observer, including the data collection format, coding, description, and guidance.…”
Section: Work Sampling Methodsmentioning
confidence: 99%
“…However, another study showed that the time nurses spent charting was not statistically changed when they used computers for documentation. 10 A study 14 revealed that during the implementation of an electronic medical records system, the total percentage of the nursing documentation was 15.8% (10.6% on paper and 5.2% on the computer), and the percentages of time spent on different categories of bedside care and indirect care were significantly related to the day and night shift. Another 15 explored the nursing activity patterns 1 month (time 1) and 1 year (time 2) after the implementation of a nursing information system.…”
Section: Impact Of Information Systems On Nursing Activity Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another benefit is decreased time spent charting. One team of researchers reported that nurses spent 10.6% of their time documenting when charting on paper but only 5.2% on computer charting (Korst, Eusebio-Angeja, Chamorro, Aydin, & Gregory, 2003). Zolot (1999) estimated a much higher number for paper charting, asserting that as much as 50% of nursing time is spent documenting on paper.…”
Section: Computerized Charting Systemsmentioning
confidence: 99%